2021
DOI: 10.33394/bjib.v9i1.3437
|View full text |Cite
|
Sign up to set email alerts
|

Uji Aktivitas Ekstrak Etanol Biji Buah Merah (Pandanus conoideus Lamk.) terhadap Bakteri Escherichia coli dan Staphylococcus aureus

Abstract: Infectious diseases can be caused by one of four different organisms, namely: bacteria, fungi, viruses, and parasites. This study aims to determine the ability and concentration of the best ethanol extract of red fruit seeds (Pandanus conoideus Lamk.) In inhibiting the growth of Escherichia coli and Staphylococcus aureus infectious bacteria. This research is an experimental study using a completely randomized design (CRD). The stages of work carried out consisted of: sample preparation, sample extraction, solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…The increase in the SPF value which is not proportional to the TFC value in this study might be due to the AlCl3 method for TFC test is only able to detect flavonoids from flavones and flavonols subgroup, while the anthocyanidins (cyanidins), flavanols (catechin), flavanones (naringenin) [36] which also contained in papaya seeds were not detectable [37].…”
Section: Resultscontrasting
confidence: 55%
“…The increase in the SPF value which is not proportional to the TFC value in this study might be due to the AlCl3 method for TFC test is only able to detect flavonoids from flavones and flavonols subgroup, while the anthocyanidins (cyanidins), flavanols (catechin), flavanones (naringenin) [36] which also contained in papaya seeds were not detectable [37].…”
Section: Resultscontrasting
confidence: 55%
“…Several studies reported the pharmacological effects of red fruit extract as antimicrobial, both as an anti-fungal, anti-bacterial, and as an anti-viral agent including as inhibitory power on Escherichia coli and Staphylococcus aureus bacteria (Asrianto et al 2021;Tharukliling et al 2021), Streptococcus mutant, Streptococcus saungunis (Damayanti et al 2020) and Enterococcus faecalis (Herdiyati et al 2020). Red fruit extract contains chemical compounds of flavonoids, tannins, alkaloids, steroids, and triterpenoids.…”
Section: Discussionmentioning
confidence: 99%
“…1 Fungi and bacteria are the most important causative agents of these infectious diseases. 2 Bacteria often infect humans. Staphylococcus aureus and Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%